Producing Printability: Articulation Work and Alignment in 3D Printing. (2nd September 2019) - Dew, Kristin N; Landwehr-Sydow, Sophie; Rosner, Daniela K; Thayer, Alex; Jonsson, Martin
Abstract : Three-dimensional printing is widely celebrated as enabling open design and manufacturing practice. With easy-to-use techniques such as automated modeling, fabrication machines ostensibly help designers turn ideas into fully fledged objects. Prior HCI literature focuses on improving printing through optimization and by developing printer and material capabilities. This paper expands such considerations by asking, how do 3D printing practitioners understand and create "printability?" And how might HCI better support the work that holds together printing workflows and changing ecosystems of materials and techniques? We conducted studies in two sites of open design: a technology firm in Silicon Valley, California and a makerspace in Stockholm, Sweden. Deploying workshops and interviews, we examine how practitioners negotiate the print experience, revealing a contingent process held together by trial and error exploration and careful interventions. These insights point to the value of tools and processes to support articulation work, what Strauss and colleagues have called the acts of fitting together people, tasks, and their ordering to accomplish an overarching project. We show that despite the sought-after efficiencies of such manufacturing, 3D printing entails articulation work, particularly acts of alignment, exposing messy modes of production carried out by a varied cast of practitioners, machines, and materials.